Microgrid control methods toward achieving sustainable energy management - Roslan M.F.; Hannan M.A.; Ker P.J.; Uddin M.N. (Elsevier Ltd, 2023)
Electric power system control; Electric power transmission networks; Energy conservation; Energy conversion; Energy management; Energy utilization; Environmental technology; Maximum power point trackers; Quality control; Renewable energy resources; Smart power grids; Stochastic systems; Sustainable development; Control methods; Maximum power point tracking controls; Micro grid; Operation and management; Renewable energy source; Sustainable energy; Sustainable energy management; Technological development; Energy management systems; algorithm; alternative energy; control system; energy efficiency; methodology; operations technology; power generation; quality control; smart grid; stochasticity; sustainability; sustainable development; technological development